2010
DOI: 10.1007/s12665-010-0889-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scale dependence of sediment dynamics in a gullied rolling loess region on the Loess Plateau in China

Abstract: Sediment dynamics is still imperfectly understood, especially at spatial scale in the highly erodible region of the Loess Plateau, and few studies have been heretofore conducted. Using 5-year continuous water and sediment records, three plots and three basins in the gullied rolling loess region were selected and sediment dynamics at spatial scale was studied. Results showed that the floods, where the peak discharge (Q p ) did not come earlier than the sediment peak, were predominant in slope zones, occupying [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Rodriguez-Blanco et al [6] similarly found clockwise to be the dominant hysteresis pattern suggesting a localized sediment sources. In contrast to these findings, Fang et al [14] showed clockwise patterns at the hillslope plot scale and counterclockwise patterns at the basin scale suggesting a dominantly hillslope source at various spatial scales on the Loess Plateau of China. The difference in results between this work and Fang et al is likely because their site has some of the highest soil erosion rates in the world with an average annual sediment yield of 22,200 tons per km 2 and extremely steep slopes of up to 70 degrees [14].…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Rodriguez-Blanco et al [6] similarly found clockwise to be the dominant hysteresis pattern suggesting a localized sediment sources. In contrast to these findings, Fang et al [14] showed clockwise patterns at the hillslope plot scale and counterclockwise patterns at the basin scale suggesting a dominantly hillslope source at various spatial scales on the Loess Plateau of China. The difference in results between this work and Fang et al is likely because their site has some of the highest soil erosion rates in the world with an average annual sediment yield of 22,200 tons per km 2 and extremely steep slopes of up to 70 degrees [14].…”
Section: Resultsmentioning
confidence: 80%
“…In contrast to these findings, Fang et al [14] showed clockwise patterns at the hillslope plot scale and counterclockwise patterns at the basin scale suggesting a dominantly hillslope source at various spatial scales on the Loess Plateau of China. The difference in results between this work and Fang et al is likely because their site has some of the highest soil erosion rates in the world with an average annual sediment yield of 22,200 tons per km 2 and extremely steep slopes of up to 70 degrees [14]. In comparison, sediment yields in the central Sierra Nevada have been estimated to be around 4.1 tons per km 2 [3].…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…During flood events, the relationship between sediment transport and discharge is not normally homogenous, often producing hysteretic loops (diCenzo and Luk, 1997; D'Agostino and Lenzi, 1999;Rickenmann, 2001;Seeger et al, 2004;Lefrancois et al, 2007;Rodríguez-Blanco et al, 2008;Soler et al, 2008;Mao et al, 2014), which have been identified between discharge and sediment transport on the Loess Plateau (Fang et al, 2008(Fang et al, , 2011(Fang et al, , 2015Fan et al, 2013). However, the role of hysteretic loops for check dams remains unclear.…”
Section: Introductionmentioning
confidence: 99%